Investigation of Blood Count-Based Inflammatory Biomarkers as Predictors of Response to Dupilumab Treatment in Patients with Chronic Rhinosinusitis with Nasal Polyps - Michael Habenbacher; Ulrich Moser; Ahmed Abaira; Peter Kiss; Clemens Holzmeister; Jakob Pock; Katharina Walla; Angelika Lang; Alexandros Andrianakis (Pharmaceutics)
Background/Objectives: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a type 2 inflammatory disease often resistant to standard treatments. Dupilumab, a monoclonal antibody targeting the IL-4α receptor, has shown efficacy in CRSwNP, but a significant subset of patients do not respond to this therapy. This study aims to investigate pretreatment complete blood count (CBC)-based inflammatory biomarkers as predictors of response to dupilumab in patients with CRSwNP. Methods: This mono-centric, retrospective, single-arm longitudinal cohort study included 80 patients with uncontrolled CRSwNP who received dupilumab treatment at the Medical University of Graz. Patients were classified into responder and non-responder groups based on a reduction of >1 in nasal polyp score (NPS) and a sinonasal outcome test-22 (SNOT-22) score <40 points at six months. Pretreatment CBC-derived biomarkers, including eosinophil count, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammation indices including the aggregate inflammation systemic index (AISI), systemic inflammation index (SII), and systemic inflammation response index (SIRI), were analyzed for their predictive value. Results: Of the 80 patients, 72.5% were classified as responders, while 27.5% were non-responders. A significant positive correlation was found between baseline eosinophil count and NPS reduction (p = 0.027), suggesting that higher eosinophil levels may predict higher NPS reduction in dupilumab treatment. However, no significant associations were observed between NLR, PLR, and systemic inflammation indices with treatment outcomes. Conclusions: Pretreatment eosinophil count may serve as a potential biomarker for predicting nasal polyp reduction in dupilumab treatment of CRSwNP. Other CBC-based inflammatory markers did not show significant predictive value. Further prospective studies are needed to validate these findings and explore additional, reliable biomarkers to optimize treatment outcomes for CRSwNP patients.